Fragility assessment of building structural systems in Mid-America. - Ellingwood, Bruce R. (Earthquake engineering & structural dynamics.)
Uncertainty in response of buildings and other civil infrastructure to earthquake ground motion is due to the inherent randomness in the ground motion itself?peak intensity, time-varying amplitude and strong-motion duration, and frequency content?and local design and construction practices. In the recently completed SAC project and ongoing research in the Pacific Earthquake Engineering Research (PEER) Center, the focus is on performance of buildings designed for regions of high seismicity. In contrast, current research in the Mid-America Earthquake (MAE) Center is examining the potential impact of earthquakes on building construction in regions of low-to-moderate seismicity in the Central and Eastern United States (CEUS) where design and construction practices seldom have made provision for earthquake resistance. This paper assesses the seismic fragilities of several typical low-to-mid-rise steel and reinforced concrete buildings representative of design and construction practices in the CEUS. A comparison of these fragilities with those incorporated in HAZUS carries implications for damage and loss estimation in this region.